Efficacy of lung cancer screening at the American University of Beirut Medical Center - Harb, Tarek; Alhafi, Anas; Tfayli, Arafat H. (Frontiers in Oncology, 2023)
Introduction In Lebanon, a dedicated screening program for lung cancer is absent. Screening is largely based on the recommendation of an informed physician or the initiative of a patient. To better understand the situation, it is important to look at the available data on patients currently being screened for lung cancer in this country. Our aim in this study is to review the data and compare it with that in the literature as well as to assess the efficacy of the screening process followed. Methods Our study accessed the electronic medical records of patients at the American University of Beirut Medical Center (AUBMC), a tertiary care center in Lebanon. We collected information on patients who underwent screening low-dose computed tomography (LDCT) scan between June 2019 and June 2021 inclusive. Records of all patients who underwent a non-contrast computed tomography (CT) scan at AUBMC during this period were collected and analyzed. Results On average, our population had a 52.6 pack-year smoking history. Moreover, 47% of our population had an accurate pack-year reported, while 12% did not have enough information to even estimate their pack-year history. When looking at the accurate and estimated data, 5% of our population did not even meet the ≥20 pack-year smoking history. Eight patients had positive findings on the screening LDCT, which we defined as suspicious findings that require further workup (e.g., PET/CT or biopsy) or other significant incidental findings. Conclusion A well-organized program for lung cancer screening in Lebanon is absent. Screening largely depends on the initiative of the physician or the patient. We were able to uncover multiple flaws in the screening method used, including poor documentation and follow-up. Although the screening method adopted retained some benefits in terms of detecting early malignancy, it lacked proper organization and was not ideal. A better, systematized screening program is needed to have optimal outcomes.